A Study of Planning and Control Volume I - Planning Commission (Planning Commission, 1966)
There is no question that there is a market potential for Indian Shipping, enough for major expansion by both public and private sector enterprises. It saves and earns foreign exchange; and, if the right sales approaches are used, can be developed without a long wait. Studies on improving the efficacy of the present sales planning, organization, and procedures are underway at S.C.I., to achieve its maximum portion of the market, and to grow as rapidly as possible.
Management Group Committee on plan Projects
Management Group Committee on plan Projects